Alih Kode dan Variasi Bahasa dalam Penulisan Takarir di Instagram: Penelitian Sosiolinguistik - Achmad Japar Nursabit; Yanty Wirza (Departement of Mathematics Education, 2025)
On Instagram, code-switching has become an intriguing subject of study because users often employ more than one language or even a mix of languages and visual elements (such as emojis) in their posts. The purpose of this research is to identify the types of code-switching commonly occurring in Instagram content and to explore the reasons influencers engage in code-switching. This study adopts a qualitative descriptive design to describe and analyze language use practices in Instagram posts. The findings reveal three types of code-switching: inter-sentential switching, intra-sentential switching, and emblematic switching. Furthermore, six reasons for code-switching were identified: discussing a specific topic, emphasizing a point, using interjections, repeating for clarification, clarifying speech content for the audience, and expressing group identity.